2020
DOI: 10.3390/ijms21031076
|View full text |Cite
|
Sign up to set email alerts
|

Root Proteomic Analysis of Two Grapevine Rootstock Genotypes Showing Different Susceptibility to Salt Stress

Abstract: Salinity represents a very limiting factor that affects the fertility of agricultural soils. Although grapevine is moderately susceptible to salinity, both natural causes and agricultural practices could worsen the impact of this abiotic stress. A promising possibility to reduce this problem in vineyards is the use of appropriate graft combinations. The responses of grapevine rootstocks to this abiotic stress at the root level still remain poorly investigated. In order to obtain further information on the mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Membrane‐localised pyrophosphatase, such as the cation stimulated tonoplast V‐PPase (Walker and Leigh 1981a, Rea and Poole 1993) and the predominantly anion stimulated tonoplast V‐ATPase (Walker and Leigh 1981b), may also have roles in maintaining intracellular ion gradients between the cytoplasm and vacuole. In grapevine, the possible roles of H + ‐ATPases and VPPase in salt tolerance have not yet been clarified, although proteomic analysis on the rootstock M4 may support a possible function of grapevine ATPases in Na + vacuolar internalisation (Prinsi et al 2020).…”
Section: Mechanisms Of Salt Tolerance In Grapevinementioning
confidence: 99%
See 1 more Smart Citation
“…Membrane‐localised pyrophosphatase, such as the cation stimulated tonoplast V‐PPase (Walker and Leigh 1981a, Rea and Poole 1993) and the predominantly anion stimulated tonoplast V‐ATPase (Walker and Leigh 1981b), may also have roles in maintaining intracellular ion gradients between the cytoplasm and vacuole. In grapevine, the possible roles of H + ‐ATPases and VPPase in salt tolerance have not yet been clarified, although proteomic analysis on the rootstock M4 may support a possible function of grapevine ATPases in Na + vacuolar internalisation (Prinsi et al 2020).…”
Section: Mechanisms Of Salt Tolerance In Grapevinementioning
confidence: 99%
“…An analysis of M4 under saline irrigation showed an increase of proteins related to carbohydrate catabolism and an increased activity of ATP and coenzyme biosynthesis pathways (Prinsi et al 2020), potentially indicating a metabolic shift to supply the energy needed for the salt stress responses, while being restricted by photoinhibition (Munns et al 2020). The M4 rootstock has also been shown to display a higher amount of enzymes related to ROS scavenging and secondary metabolism, which may relate to increases in antioxidative activity (Prinsi et al 2020). No apparent increase in ion transport proteins was observed, however, which may relate to the higher leaf ion accumulation that has been observed for the M4 variety previously (Meggio et al 2014).…”
Section: Studies On Salt Tolerance In Grapevine Rootstocksmentioning
confidence: 99%
“…In a subsequent study, Henderson et al (2018), successfully mapped a QTL that controls Na + exclusion in rootstocks and identified the causal gene ( VisHTK1;1 ) underlying that trait; these findings may assist with breeding Na + tolerant grapevine rootstocks. Recently, Prinsi et al (2020) characterised the root‐level response to salt stress of two grapevine rootstocks (M4 and 101‐14), indicating that M4 had a greater capability to maintain and adapt energy metabolism and to sustain the activation of salt‐protective mechanisms, while, in 101‐14, the energy metabolism was deeply affected and an evident induction of the enzymatic antioxidant system occurred. Overall, the information provided by this group of studies constitutes the basis for further research on the performance of different graft combinations against salt stress.…”
Section: Challenges Related To Abiotic Stressesmentioning
confidence: 99%
“…Therefore, the selection of new rootstocks could be an interesting solution to overcome some of the risks associated with salinity, such as preventing excess of Cl − and Na + in leaves and bunches, and the subsequent negative effect on yield and fruit composition, and should rely on the research efforts mentioned in this section (Gong et al 2014, Henderson et al 2018, Prinsi et al 2020), despite these being restricted to only three genotypes. In this context, a recent survey (Heinitz et al 2020) identified promising Cl − ‐excluding accessions within a collection of Vitis species native to south‐western USA and northern Mexico.…”
Section: Challenges Related To Abiotic Stressesmentioning
confidence: 99%
“…In the present work, we adopted biochemical and proteomic approaches to analyze, in the root of M4 grapevine rootstock, the responses occurring after the addition of NO 3 − to the nutrient solution in hydroponics. This rootstock genotype was selected on the basis of its good response to abiotic stress [ 31 , 32 , 33 , 34 , 35 ], which is contributing to the expansion of its use in viticulture. The biochemical evaluations were devoted to verifying the role played by roots in the response to NO 3 − resupply, monitoring key parameters.…”
Section: Introductionmentioning
confidence: 99%